The transplacental transfer efficiency of per- and polyfluoroalkyl substances (PFAS): a first meta-analysis. (2nd January 2022) - Appel, Mareike; Forsthuber, Martin; Ramos, Romualdo; Widhalm, Raimund; Granitzer, Sebastian; Uhl, Maria; Hengstschläger, Markus; Stamm, Tanja; Gundacker, Claudia
ABSTRACT: Per- and polyfluorinated substances (PFAS), ubiquitously present in the environment and biota, are transferred to the fetus via the placenta. PFAS can be distinguished, among other things, by their different carbon chain lengths and functional groups. The aim of this study was to provide comprehensive evidence on PFAS transfer rates across the human placental barrier by means of a meta-analysis based upon a systematic review. The available literature up to April 2021 was reviewed and transplacental transfer efficiencies (TTEs) of PFAS assessed. A total of 39 studies reporting data on 20 PFAS were included in the systematic review. Of these, 20 studies with data on 19 compounds were included in the meta-analysis. Comprehensive Meta-Analysis (CMA v3.0) was used for quantitative, statistical analyses with random effects models. A curvilinear relationship was found with short and long chains of perfluorocarboxylic acids (PFCAs) exhibiting higher TTE than compounds with intermediate chain length. Among the less well studied PFAS, perfluorohexanoic acid (PFHxA), 6:2 fluorotelomersulfonic acid (6:2 FTS) and perfluorobutanoic acid (PFBA) stood out the most with a high TEEs. The dependence of TTEs on chain length and functional group is clearly shown in this first meta-analysis on PFAS transfer across the human placenta. More data on effects of less well studied PFAS in pregnant women and neonates are needed to assess the potential risk for fetal exposure. Graphical abstract: uf0001